The Relationship of Dietary Intake and Nutritional Status to the Risk of Eating Disorders among University Students in Yogyakarta, Indonesia - Habibah, Nurina; Amri, Aisyah Novita; Kusuma, Rio Jati (JURNAL GIZI DAN KESEHATAN, 2025)
Eating disorders are linked to poor nutritional status, often driven by dietary inadequacies such as caloric restriction or unhealthy eating behaviors. A university student was a vulnerable group in terms of susceptible to develop eating disorders. Understanding how dietary intake and nutritional status contribute to eating disorders’ risk is essential. This study aim to examining the relationship between dietary intake, nutritional status, and eating disorders’ risk among university students in Yogyakarta, Indonesia. We conducted a cross-sectional study in June-August 2024, assessing dietary intake via a 24-hour food record and analyzing nutritional status by body mass index (BMI). Eating disorders’ risk was measured using the EAT-26 questionnaire. Results indicated that 90.4% of students had deficient dietary intake, 4.8% low dietary intake, and the rest were moderate and adequate. While 11.9% students were underweight, 52.4% had normal BMI, and the remainder were overweight or obese. Dietary intake did not significanly related with eating disorders’ risk, but nutritional status significantly relateated (p 0.033). In conclusion, most participants had energy intake deficits but dietary intake was not significantly associated to eating disorders’ risk. Nutritional status, however, was significantly associated with eating disorders’ risk, with underweight individuals being particularly vulnerable.